Modern methods in solid-state NMR : a practitioner's guide - Hodgkinson, Paul (New developments in NMR ;, 2018)
The volume focuses on topics relevant to the developing field of "NMR crystallography", that is the use of solids NMR as a complement to diffraction crystallography, and will be of interest to every solid-state NMR researcher working in the chemical sciences